A new species and new records of Dorstenia (Moraceae, Dorstenieae) from Rwanda, East Africa - Fischer, Eberhard; Killmann, Dorothee (Phytotaxa, 2015)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–> The new species Dorstenia marijanmatokii from Rwanda is described. It differs from Dorstenia nyungwensis in the discoid and entirely purple receptacle with shorter primary appendages and more numerous and irregular secondary appendages, and the densely tomentose lower leaf surface with purple venation. First records of Dorstenia brownii and D. psilurus from Rwanda and a key to the species of Dorstenia for Rwanda are provided. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>